2021
DOI: 10.2217/bmm-2019-0537
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Admission Blood Fibrinogen-To-Albumin Ratio and Clinical Outcomes After Acute Lacunar Stroke

Abstract: Aim: We aimed to investigate the influence of admission fibrinogen-to-albumin ratio (FAR) on 3-month outcomes after acute lacunar stroke. Materials & methods: Consecutive patients with acute lacunar stroke were included and classified into two groups according to an optimized FAR cut-off value determined by receiver operating characteristic curve analysis. Results: Compared with those with low FAR (<0.077), patients from the high FAR group (≥0.077) had significantly higher risk for 3-month disability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Fibrinogen is closely related to thrombosis, and high fibrinogen levels are often regarded as biomarkers of vascular diseases such as myocardial infarction or stroke [ 24 ]. Some studies [ 25 27 ] have shown that high levels of fibrinogen can predict the occurrence and clinical prognosis of LCI, which further supports the results of this study, suggesting that fibrinogen can effectively predict the combination of LCI in elderly patients with a femoral neck fracture. Scr is one of the most commonly used indicators of kidney function.…”
Section: Discussionsupporting
confidence: 88%
“…Fibrinogen is closely related to thrombosis, and high fibrinogen levels are often regarded as biomarkers of vascular diseases such as myocardial infarction or stroke [ 24 ]. Some studies [ 25 27 ] have shown that high levels of fibrinogen can predict the occurrence and clinical prognosis of LCI, which further supports the results of this study, suggesting that fibrinogen can effectively predict the combination of LCI in elderly patients with a femoral neck fracture. Scr is one of the most commonly used indicators of kidney function.…”
Section: Discussionsupporting
confidence: 88%
“… 30 Recently, Zheng et al specified that the FAR was associated with the severity and was a predictor of a poor 3-month outcome in patients with acute lacunar cerebral infarction. 10 Our study also showed that the FAR was associated with a poor 3-month clinical outcome of acute pontine infarction and further confirmed that the FAR was positively correlated with both the baseline NIHSS score and the mRS score. Patients with a high FAR had more severe neurological deficits and a worse outcome.…”
Section: Discussionsupporting
confidence: 83%
“…Zheng et al indicated that a FAR value ≥ 0.077 might be a predictor of poor 3-month clinical outcomes after acute lacunar cerebral infarction. 10 However, it is not clear whether an elevated FAR is associated with poor outcomes after pontine infarction. Therefore, the main purpose of this study was to elucidate the association between the FAR and the 3-month clinical outcomes of patients with acute pontine infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The fibrinogen-to-albumin ratio (FAR) which combines coagulation with nutritional status, is a new vital inflammatory biomarker for a variety of diseases, such as cervical cancer, oligodendroglial gliomas, acute coronary syndrome, and stroke (22)(23)(24)(25). Zheng et al found that a high FAR level on admission was highly associated with 3-month mortality and disability in patients with acute lacunar stroke (22). Yet, the link between FAR and the risk of developing SAP in patients after AIS remains unclear.…”
Section: Introductionmentioning
confidence: 99%